PENGARUH KEPUTUSAN INVESTASI (PER), KEPUTUSAN PENDANAAN (DER) DAN KEBIJAKAN DEVIDEN (DPR) TERHADAP PRICE TO BOOK VALUE - Anita Ester Rahayu; Ela Widasari; Siti Mudawanah (Universitas La Tansa Mashiro, 2023)
Price to Book Value (PBV) is a ratio that can describe the comparison between the stock price and the book value of equity. The higher the PBV value, the greater the share price. This study aims to examine and analyze the effect of Investment Decisions, Funding Decisions and Dividend Policy on Price to Book Value of LQ45 companies listed on the Indonesia Stock Exchange (IDX) for the 2017- 2021 period. The data used is secondary data with the method used is the quantitative method. The population in this study amounted to 45 companies LQ45 and samples taken using purposive sampling as many as 17 companies. The analysis technique used is classical assumption test, multiple linear regression, coefficient of determination test, correlation coefficient test and hypothesis testing using SPSS v.25. The results of the analysis carried out show that partially the Investment Decision (PER) has a significant effect on PBV, then H1 is accepted. The Funding Decision (DER) has no effect on PBV, so H2 is rejected. And the Dividend Policy (DPR) has no effect on PBV, so H3 is rejected. Meanwhile, simultaneously the Investment Decision (PER), Funding Decision (DER) and Dividend Policy (DPR) affect PBV, then H4 is accepted..